Structural Analysis of Factors Influencing the Enhancement of Citizens’ Utilization of Urban Green Spaces - Fakherian, Parizad; Haghjou, Amir; Ebrahimi Asl, Hassan; Shaghaghi, Shahriar (Management Strategies and Engineering Sciences, 2026)
The present study aimed to identify and structurally analyze the environmental, social, managerial, and perceptual factors affecting the enhancement of citizens’ utilization and enjoyment of urban green spaces in Tabriz. This applied study employed a quantitative descriptive–analytical design using structural equation modeling to examine relationships among variables influencing citizens’ engagement with urban green spaces. The statistical population consisted of residents of Tabriz, from which 400 participants were selected through multi-stage cluster random sampling to ensure spatial and demographic representation. Data were collected using a researcher-developed questionnaire grounded in urban planning, environmental psychology, and green infrastructure literature. The instrument measured constructs including accessibility, environmental quality, perceived safety, recreational facilities, social interaction opportunities, management and maintenance quality, environmental awareness, and citizens’ utilization behavior. Content validity was confirmed through expert review, and reliability was verified using internal consistency indices. Data analysis was conducted using descriptive statistics, confirmatory factor analysis, and structural equation modeling to evaluate measurement validity and test hypothesized structural relationships among variables. The structural model demonstrated satisfactory goodness of fit, confirming the validity of the proposed conceptual framework. Environmental awareness exerted the strongest positive effect on citizens’ utilization of urban green spaces, followed by accessibility and environmental quality. Social interaction opportunities and recreational facilities showed significant positive impacts, indicating the importance of functional and social characteristics of green environments. Management and maintenance quality also significantly influenced utilization, highlighting the role of urban governance performance. Perceived safety had a meaningful but comparatively smaller effect, suggesting that psychological comfort contributes to sustained engagement with green spaces. Overall, all hypothesized paths were statistically supported, revealing that citizens’ benefit from urban green spaces results from the combined interaction of environmental, social, and managerial dimensions. The findings indicate that enhancing citizens’ utilization of urban green spaces requires an integrated planning approach that simultaneously addresses environmental quality, accessibility, social functionality, governance effectiveness, and environmental awareness. Urban green spaces function as socio-ecological systems whose successful performance depends on coordinated urban management and citizen-centered design strategies.